1995
DOI: 10.7326/0003-4819-122-3-199502010-00001
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Type 1b (II) Infection in France and Italy

Abstract: The prevalence of HCV genotypes in French and Italian patients has been changing; the prevalence of HCV type 1b (II) infection has progressively decreased, although it still accounts for most HCV-related cirrhosis and hepatocellular carcinoma. High HCV viremia levels and HCV genotype type 1b (II) are independent predictors for poor response to interferon-alpha therapy and should be considered in the management of patients with HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
215
5
5

Year Published

1995
1995
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 462 publications
(254 citation statements)
references
References 0 publications
29
215
5
5
Order By: Relevance
“…Patients with HCV genotype non-1 had better responses compared with patients with HCV genotype 1, across all treatment arms, as has been observed in other trials of IFN-based therapy. 1,2,6,[9][10][11] This study demonstrated that PEG(40kd) IFN ␣-2a is superior to IFN ␣-2a in the treatment of patients with CHC. The 180-g PEG(40kd) IFN ␣-2a dose was associated with the highest sustained virological and biochemical responses (36% and 38%, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…Patients with HCV genotype non-1 had better responses compared with patients with HCV genotype 1, across all treatment arms, as has been observed in other trials of IFN-based therapy. 1,2,6,[9][10][11] This study demonstrated that PEG(40kd) IFN ␣-2a is superior to IFN ␣-2a in the treatment of patients with CHC. The 180-g PEG(40kd) IFN ␣-2a dose was associated with the highest sustained virological and biochemical responses (36% and 38%, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…[25][26][27][28] In Italy, type 1b is the most common, accounting for more than 60% of infected cases. [29][30][31] In our control population (healthy blood donors and patients with chronic liver disease, CLD), genotype 1b was present in 64% of cases, with each of the other genotypes being present in less than 10% of cases. The clinicopathologic correlation of specific genoptypes is currently the subject of active investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be seen whether or not such clinically important features of genotype II/lb are shared by other genotypes in genetic group 1. Some groups of investigators report differences in the response to interferon between patients infected with HCV genotype I/la and those infected with II/lb (Qu et al, 1994;Nousbaum et al, 1995), while others do not (Mahaney et al, 1994). Additional clinical and therapeutic trials are required to settle this.…”
Section: Discussionmentioning
confidence: 99%